Defining the Business Philosophy Foundation for Sustainable Business Education - Muhammad Ade Kurnia Harahap; Suherlan Suherlan; Syamsu Rijal; Abu Muna Almaududi Ausat (Departement of Mathematics Education, 2023)
Sustainable business education is an approach to teaching business that focuses on sustainability. In recent years, issues such as climate change, the sustainability of natural resources, and the social responsibility of business have become a growing concern around the world. In this context, research on defining the philosophical foundations of sustainable business will help identify and evaluate key aspects of a sustainable business philosophy and also discuss the practical implications of its use in business education. This research is qualitative in nature. Data collection techniques included listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study concluded that in an effort to prepare a generation that is ready to face future business challenges, business education institutions should take steps to create a foundation for a sustainable business philosophy. This includes adopting a sustainable approach in the education curriculum, creating an enabling environment for sustainable business development, and introducing concepts such as sustainability, long-term perspective, and corporate social responsibility.